PARAMETRES OF FORMING THE CULTURAL OUTLOOK OF LEARNERS (Scientific journal of the Fergana State University, 2023)
The article touches upon the issues of forming the cultural outlook of learners and the role of a teacher in this process. Furthermore, the pedagogical requirements and capabilities, related to forming the cultural outlook of learners, have been analyzed